Classical effect for enhanced high harmonic yield in ultrashort laser pulses with a moderate laser intensity. (28th February 2017) - Shi, Y Z; Wang, S; Dong, F L; Li, Y P; Chen, Y J
Abstract: We study the influence of pulse duration on high harmonic generation (HHG) by exploring a wide laser-parameter region theoretically. Previous studies have shown that for high laser intensities close to  saturation ionization intensity, the HHG inversion efficiency is higher for shorter pulses since the ground-state depletion is weaker in short pulses. Our simulations show that this high efficiency also appears for a moderate laser intensity at which the ionization is not very strong. A classical effect relating to shorter travel distances of the rescattering electron in shorter pulses is shown to contribute importantly to this high efficiency. The effect can be amplified significantly if a two-color laser field is used, suggesting a potential approach to increasing the HHG yield and generating short and bright attosecond pulses.